ASEAN’s Role in the Management of the Defense Industry in the Region - Sulistiyanto; Purwantoro, Susilo Adi; Mualim, Much (Advances in Social Sciences Research Journal, 2023)
The problem of ASEAN as a regional organization is inseparable from the problems of the Indo-Pacific region. These issues include the South China Sea, AUKUS, and competition between the United States and China. These problems force ASEAN to develop its defense potential through defense industry collaboration. The method used in this study is qualitative. The Indo-Pacific region where ASEAN is located is a very complex, vulnerable, and dynamic region given its strategic position, natural resources, and the large number of actors playing both economic, and defense security that greatly affects the security stability of the region. ASEAN Defense Industry Collaboration is a form of ASEAN’s commitment as a regional organization to maintain stability in the region. The collaboration is called the ASEAN Defence Industrial Collaboration (ADIC) to create a comprehensive and consolidated security and defense environment in Southeast Asia.